1999
DOI: 10.1186/cc360
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Nutritional support has become a routine part of the care of the critically ill patient. It is an adjunctive therapy, the main goal of which is to attenuate the development of malnutrition, yet the effectiveness of nutritional support is often thwarted by an underlying hostile metabolic milieu. This requires that these metabolic changes be taken into consideration when designing nutritional regimens for such patients. There is also a need to conduct large, multi-center studies to acquire more knowledge of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(8 citation statements)
references
References 111 publications
0
8
0
Order By: Relevance
“…This overall lipid synthetic process is called lipogenesis. 7) In this study, prolonged HFD consumption did not increase, but rather decreased, the mRNA levels of various genes involved in adipogenesis, such as PPARg2, aP2, SREBP1c, FAS, and an enzyme that catalyzes the rate-limiting step of cholesterol biosynthesis, HMGR, in the visceral adipose tissue of rats. These results correspond to the previous observation that the expressions of adipogenesis-related genes, including PPARg, SREBP1c, and their target genes (FAS and ACC), decreased in the adipose tissue of a longterm high-fat-diet-fed dog 28) or ob/ob mice 29,30) compared with their lean controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This overall lipid synthetic process is called lipogenesis. 7) In this study, prolonged HFD consumption did not increase, but rather decreased, the mRNA levels of various genes involved in adipogenesis, such as PPARg2, aP2, SREBP1c, FAS, and an enzyme that catalyzes the rate-limiting step of cholesterol biosynthesis, HMGR, in the visceral adipose tissue of rats. These results correspond to the previous observation that the expressions of adipogenesis-related genes, including PPARg, SREBP1c, and their target genes (FAS and ACC), decreased in the adipose tissue of a longterm high-fat-diet-fed dog 28) or ob/ob mice 29,30) compared with their lean controls.…”
Section: Discussionmentioning
confidence: 99%
“…6) Differentiated adipocytes store fatty acids in the form of triglycerides in their cytoplasm, with the involvement of various enzymes such as strearoyl-CoA desaturase-1 and fatty acid synthase (FAS). 7) AMP-activated protein kinase (AMPK) stimulates the pathways that increase energy production such as glucose transport and fatty acid oxidation, and switches off the pathways that consume energy such as lipogenesis, protein synthesis, and gluconeogenesis. 8) The uncoupling proteins (UCPs), present in the mitochondrial inner membrane, mediate a controlled discharge of the proton gradient that is produced by the respiratory chain.…”
mentioning
confidence: 99%
“…6 TGs are synthesized in the liver, secreted into the bloodstream, and transported to the peripheral organs, including adipose tissue. 7,8 Several recent studies have demonstrated that hepatic TG availability is controlled by the balance between FAS and oxidation in the liver.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Studies also indicate that high glucose nutritional regimes often result in excess blood glucose [7][8][9][10][11][12][13], representing another source or cause of hyperglycaemia.…”
Section: Hyperglycaemia In Critical Carementioning
confidence: 99%
“…However, when insulin effect saturates, effective glycaemic control may still be enabled by controlling the exogenous nutritional inputs that may otherwise be exacerbating the original problem [7][8][9][10][11][12][13].…”
Section: Model-based Controlmentioning
confidence: 99%